2018
DOI: 10.1021/acscatal.8b03093
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Photocatalysis for Selective Formation of High-Value-Added Molecules: Some Chemical and Engineering Aspects

Abstract: This review deals with the parameters that influence heterogeneous photocatalysis (PC) for selective synthesis of high-value chemicals by itself or in combination with other technologies. In particular, the parameters related to the photocatalysts, such as crystallinity degree, type of polymorph, surface acid–base properties, exposure of particular crystalline facets, coupling of different semiconductors, position of the valence and conduction band edge, addition of doping agents, and those related to the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(96 citation statements)
references
References 297 publications
(466 reference statements)
0
96
0
Order By: Relevance
“…In addition, there are a number of works in which TiO 2 -based photocatalysts were used to neutralize harmful to the atmosphere gases [ 6 , 7 , 8 , 9 ]. Chemical stability, easy accessibility, nontoxicity and the ability to oxidize under the influence of radiation, allow TiO 2 -based photocatalysts to solve the main global problems associated with pollution of the environment and need for renewable energy [ 10 , 11 ]. Currently, TiO 2 as a photocatalyst is commercially produced in powder form.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are a number of works in which TiO 2 -based photocatalysts were used to neutralize harmful to the atmosphere gases [ 6 , 7 , 8 , 9 ]. Chemical stability, easy accessibility, nontoxicity and the ability to oxidize under the influence of radiation, allow TiO 2 -based photocatalysts to solve the main global problems associated with pollution of the environment and need for renewable energy [ 10 , 11 ]. Currently, TiO 2 as a photocatalyst is commercially produced in powder form.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most impedimental factors of photocatalytic industrial water treatment is the immobilization of the semiconductor to eliminate the separation/filtration costs [ 1 ]. In most cases, UV active titanium dioxide was used in photocatalytic water purification applications and on the semi-industrial scale (both immobilized and in suspension as well) [ 2 , 3 , 4 , 5 ]. This material has some advantages and disadvantages [ 6 ], but it is much more critical to solve the immobilization related problems.…”
Section: Introductionmentioning
confidence: 99%
“…mineralize) efficiently almost every organic pollutant, in the last decade photocatalytic processes have been mainly applied in the field of environmental remediation [13][14][15]. Despite that, in last decade some studies have been carried out on the application of photocatalysis for synthesis such as selective reduction and oxidation [16][17][18], hydrogen production [19][20][21] and CO 2 conversion [22,23] to develop, in perspective, environmentally benign synthetic processes. These studies demonstrated that interesting selectivity can be obtained by using photocatalytic processes in comparison to conventional methods by appropriately selecting some photocatalytic parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%